기상조건이 적외선 열화상에 미치는 영향 분석 - 林庸培(Young-Bae Lim); 金基鉉(Gi-Hyun Kim); 崔明日(Myeong-Il Choi); 朴治現(Chee-Huyn Park); 裵錫銘(Seok-Myung Bae); 趙成元(Sung won Cho) (전기학회 논문지 P권, 56(3), 2007)
Infrared thermography is one of the most valuable and cost-effective diagnostic techniques for predictive maintenance on electrical systems. For the electric installations, the thermographies can identify major problems, which if left unattended could lead to breakdowns. The result thermal images depend upon operator skills, inspection technique, and load and weather conditions. When the thermographer is applied to remote monitoring, the conditions of the systems are not perfectly analyzed because operators are hard to know the weather's effects of the installed place. Therefore, this paper defines the effects by weather conditions which will influence the final results. The purpose of this paper is to define the weather effects that a thermographer needs to consider for successful condition analysis.